Cynatratoside-C from Cynanchum atratum displays anti-inflammatory effect via suppressing TLR4 mediated NF-κB and MAPK signaling pathways in LPS-induced mastitis in mice. (5th January 2018) - Hu, Ge; Hong, Dong; Zhang, Tao; Duan, Huiqin; Wei, Panying; Guo, Xinxin; Mu, Xiang
Abstract: The present study was conducted to isolate anti-inflammatory compound from Cynanchum atratum and investigate the molecular mechanisms of active compound against lipopolysaccharide (LPS)-induced mastitis in mice. Bioassay-guided fractionations and isolation (via ex vivo tests) of compounds with anti-inflammatory activity were performed on roots of C. atratum yielding a pure bioactive compound: Cynatratoside-C, identified by comparing spectral data (EI-MS, 1 H NMR and 13 C NMR) with literature values. Ex vivo tests showed that Cynatratoside-C inhibited the expression of TLR4 and pro-inflammatory cytokine (TNF-α, IL-6 and IL-1β) production in LPS-stimulated primary mouse mammary epithelial cells. In vivo results indicated that Cynatratoside-C markedly attenuated LPS-induced mammary histopathologic changes and mammary oxidative stress (MDA, SOD, GPx) activity. Besides, Cynatratoside-C blocked the expression of Toll-like receptor 4 (TLR4) and then suppressed the phosphorylation of nuclear transcription factor-kappa B (NF-κB) p65 and degradation inhibitor of NF-κBα (IκBα). Further study showed that Cynatratoside-C could suppress the phosphorylation of p38, extracellular signal-regulated kinase (ERK) and c-jun NH2-terminal kinase (JNK) in mitogen-activated protein kinase (MAPK) signal pathway. In conclusion, our results suggest that Cynatratoside-C played an anti-inflammatory role in LPS-induced mastitis by regulating TLR4 and the NF-κB and MAPK signaling pathways in mammary gland tissues. Cynatratoside-C may be a promising potential therapeutic reagent for the treatment of mastitis. Graphical abstract: Highlights: Cynatratoside-C was isolated from C. atratum by bioassay-guided isolation. Cynatratoside-C attenuated LPS-induced mammary histopathologic changes and mammary oxidative stress. Cynatratoside-C displays anti-inflammatory effect via suppressing TLR4 mediated NF-κB and MAPK signaling pathways.